Between `Empowerment' and `Liberation': The Kudumbashree Initiative in Kerala - J. Devika and Binitha V. Thampi (Indian Journal of Gender Studies 2007; 14; 33, 2007)
Micro-finance and its (purported) capacity to empower women is by now a wellexplored field all over the world. We now have several tools by which micro-finance programmes may be assessed. However, here we attempt to critically assess the claims of the Kerala government's poverty eradication programme, the Kudumbashree, which combines a micro-finance model with other elements through critical feminist lenses. Further, we attempt to place this programme within Kerala's own historical experience of empowering the poor. Given the fact that this major effort to popularise microfinance in Kerala has the twin aims of poverty alleviation and women's empowerment, this seems justified. We try to place the `micro-finance revolution' in Kerala within the larger historical trajectory of successive `regimes of empowerment' in order to understand the different political stakes in each, and their implications for gender politics. While using some of the available tools that employ indicators of gender effectiveness to assess the impact of micro-finance in empowering women is certainly a basic exercise, the present approach allows us to draw lessons for effective gender politics through a comparison with earlier modes of empowering the deprived classes in Kerala.